Eosinophilic gastro-enteritis in a German shepherd dog: Clinical, Haematological and Biochemical study - Minnat, T. R.; Al-Bassam, L. S.; Rasheed, Y. M. (Journal of Kerbala for Agricultural Sciences, 2017)
A 4-year-old male German shepherd dog was presented to the Vet. Clinic / Fac. Vet. Medicine / Dialala University with long past history of anorexia, chronic intermittent vomiting, hematemesis and melena. Clinical examination revealed dehydration, debilitation with generalized paleness of mucous membranes. Blood picture showed anaemia with eosinophilic leukocytosis. Biochemical parameter included mild increase in ALP, ALT and AST enzymes with normal range of creatinine and urea and a decrease in total plasma protein and increase in fibrinogen. There was an excellent animal response to treatment with Predinsolone. Recurrence of clinical signs appeared after stoppage of treatment and the condition get worse. Ultrasonographic examination revealed pathological changes in the liver and stomach of the animal. The animal died after sometime. All previous observations suggested that the case is an advanced fatal eosinophilic gastroenteritis (EG). This is the first report on canine eosinophilic gastroenteritis in Diyala Province/ Iraq.